Distance Learning in Polish Schools During the Coronavirus Lockdown: the Areas of Success and Failure Experienced by Polish Teachers of English as a FL - Wysocka-Narewska, Marzena (International Journal of Research in E-learning, 2021)
Based on Roblyer & Edwards (2000: 192), distance learning means “the acquisition of knowledge and skills through mediated information and instruction, encompassing all technologies and other forms of learning at a distance.” The instructional delivery includes an instructor who is physically located in a different place from the learner, as well as possibly providing instruction at disparate times. More specifically, the instructor controls the instructional sequencing and pacing and all learners participate in the same learning activities. The aim of the paper is to show the advantages and disadvantages of distance schooling during the Covid-19 lockdown, the emphasis being placed upon among others, the teacher – student relationship, the equipment conditions required for running an English lesson and working online, as well as some “food for thought” in the form of necessary changes and modifications to be introduced, which have been suggested by the sample in question. The respondents constitute 9 teachers from secondary schools, who have replied to an online questionnaire investigating the situation in Polish schools, concerning distance education, specifically teaching a FL. Apart from presenting the current state of affairs, some suggestions for the future are remarked upon.